A Phase I Study of Clofarabine With Multiagent Chemotherapy in Childhood High Risk Relapse of Acute Lymphoblastic Leukemia (VANDEVOL Study of the French SFCE Acute Leukemia Committee). Issue 2 (16th September 2015) - Nelken, Brigitte; Cave, Helene; Leverger, Guy; Galambrun, Claire; Plat, Genevieve; Schmitt, Claudine; Thomas, Caroline; Vérité, Cécile; Brethon, Benoit; Gandemer, Virginie; Bertrand, Yves; Baruchel, André; et al.
Abstract : Background: Current outcome of very early relapse of acute lymphoblastic leukemia (ALL) in children remains poor. As a single agent, clofarabine provided a response rate of 26% in childhood ALL second relapse and, in combination with cyclophosphamide and etoposide, a 44% complete remission and complete remission without platelet recovery (CR+CRp) rate. Further multi‐drug combinations need to be investigated. We used the VANDA regimen as a template, cytarabine being replaced by clofarabine. Patients and methods: A phase I study combining escalating doses of clofarabine (25% increments from 20 to 40 mg/m 2 /d) with fixed doses of mitoxantrone, etoposide, asparaginase, and dexamethasone was undertaken in children presenting with very early or second or post‐transplant ALL relapse. Results: Twenty patients were enrolled, 19 were evaluable. Four patients had previously been allografted. Dose‐limiting toxicity (DLT) appeared at dose level 3 (32 mg/m 2 ), one out of six patients experienced a liver DLT. At dose level 4 (40 mg/m 2 ), four DLT occurred (two fungal infection and two liver DLT). The maximum tolerated dose (MTD) of clofarabine was thus determined to be 32 mg/m 2 . There was no toxic death. Eleven (57.9%) patients achieved a CR. Six patients proceeded to allogeneic stem cell transplantation. Conclusion: Clofarabine MTD was 32 mg/m 2 /d in this combination which appeared feasible and effective in this population. Pediatr Blood Cancer © 2015 Wiley Periodicals, Inc.